A study on evaluation of biomedical waste management in a tertiary care hospital in South India - Dr. Aishwarya J Ramalingam; Dr. ChitralekhaSaikumar (Tropical Journal of Pathology and Microbiology, 2018)
Introduction: Bio-Medical wastes are classified based on their source of generation which includes various risk factors relatedto their handling and final disposal. The segregation of waste at the source of generation is the significant step.The compliance in various categories of biomedical waste management in a tertiary care hospital was evaluated.Materials and Methods: A checklist containing 17 parameters related to biomedical waste management such as ‘condition of waste containers’, ‘segregation of waste’, ‘mutilation of recyclable waste was prepared and observed for compliance in 25 different patient care areas such as 9 Operation theatres, 1 casualty, 11 wards and 4 ICU. Each area was visited on any 3 non-consecutive days in the study period of 6 months from August 2017 to January 2018. Thus, a total of 6 visits were made to each area and mean percentage scorewas analysed for each area and each category of biomedical waste management.Results:For OTs, the mean percentage for ‘condition of waste containers’, ‘segregation of waste’, ‘mutilation of recyclable waste’ was 90%, 97% and 93% respectively. In casualty, the mean percentage was 89%, 94% and 87% respectively. For wards, the meanpercentage for these categories was 88%, 93% and 89% respectively; and for ICUs, the meanpercentage was 88%, 100% and 92% respectively.Conclusion:It was determined that more importance needs to be rested for ‘mutilation of recyclable waste’ especially in wards.